Efficacy And Safety of Cannabidiol on Juvenile Diabetes Outcomes in Male Rats - Awkar, Nai (2023)
Background: Cannabidiol (CBD) is a major non-psychotomimetic cannabinoid found in the Cannabis sativa plant with several pharmacological effects. Juvenile Diabetes is a major chronic illness that affects the life of patients. CBD presents desirable effects on hyperglycemia by protecting against oxidative stress and inflammation, having neuroprotective properties, and acting on receptors linked to glycemia. Thus, CBD has the potential to decrease HbA1C in diabetic patients (Diabetes Mellitus type 1) and improve their lives. Objective: The current research aims to explore the pharmacological effect of CBD on Juvenile Diabetes in rat models, as well as the safety profile of CBD including toxicology studies on the liver and the pancreas. Methods: The research was done by conducting experiments on young adult male Wistar rats. The rats were given streptozotocin (STZ) for Juvenile Diabetes induction. The rats were randomly assigned to four experiments for a total duration of 30 days. Each experiment contained a vehicle control group alongside several groups of different dosage regimens of CBD. Each Experiment consisted of a specific and required number of animals (according to the standardized toxicity tests for rodents). Results: The animal data and findings from this study offer the opportunity for a safe and effective oral drug for the treatment of Juvenile Diabetes to be considered for further research and clinical trials. Conclusion: The animal data from this study confirmed the safety of CBD when administered in different dosing regimens per body weight with NOAEL (the no-observed-adverse-effect level) = 150mg/kg. In addition, the results gave promising insights for considering CBD as an oral treatment option for juvenile diabetes as dose-dependent. The CBD dose of 50mg/kg when administered for 14 days was able to control blood glycemia values, body weights and produce insulin concentration levels that are close to normal values.